The Role of Investment Management Institutions in Carbon Trading in Industrial Areas in Indonesia - Loudoe, Fafat Akbar; Sakti, Muthia (Journal of Law, Politic and Humanities, 2024)
Life always evolves with the times, including the country. Indonesia is developing by shifting from an agrarian to an industrial sector that is growing rapidly. The existence and development of the industry are instrumental in economic growth in Indonesia, but as the industry develops, the greenhouse gas emissions produced by Indonesia are also increasing. Therefore, a solution is needed to lower greenhouse gas emissions, and one of the solutions is carbon trading. Besides reducing carbon gas emissions, carbon trading can also encourage the domestic carbon market through its buying and selling system, opening up investment opportunities. In relation to investment, since the inauguration of the Job Creation Law, there has been an institution specifically regulating investment, namely the Investment Management Institution, representing the central government with significant authority and privileges. This study aims to analyze how the regulation of carbon trading has changed after the inauguration of the Job Creation regulation as a law and the position of the Indonesia Investment Authority in carbon trading within the industrial sector in Indonesia.